2012
DOI: 10.1186/1756-9966-31-103
|View full text |Cite
|
Sign up to set email alerts
|

FGFR-1 amplification in metastatic lymph-nodal and haematogenous lobular breast carcinoma

Abstract: BackgroundLobular breast carcinoma usually shows poor responsiveness to chemotherapies and often lacks targeted therapies. Since FGFR1 expression has been shown to play pivotal roles in primary breast cancer tumorigenesis, we sought to analyze the status of FGFR1 gene in a metastatic setting of lobular breast carcinoma, since promising FGFR1 inhibitors has been recently developed.MethodsFifteen tissue metastases from lobular breast carcinomas with matched primary infiltrative lobular breast carcinoma were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
(39 reference statements)
0
31
0
1
Order By: Relevance
“…38, 41, 42; Table 1). In breast cancer, amplification of FGFR1-and/or 11q12-14 (which contains CCND1, FGF3, FGF4, and FGF19) have been observed in 23% of hormone receptor-positive (HR þ ), 27% of HER2-amplified, and 7% of triple-negative cases and is predictive for early relapses and poor outcome (43)(44)(45)(46)(47). Many FGFR1-amplified breast cancer cell lines are addicted to FGFR1 amplification (45,48,49), and FGFR1 amplification also drives resistance to endocrine therapy (48).…”
Section: Dysregulation Of Fgfr Signaling In Human Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…38, 41, 42; Table 1). In breast cancer, amplification of FGFR1-and/or 11q12-14 (which contains CCND1, FGF3, FGF4, and FGF19) have been observed in 23% of hormone receptor-positive (HR þ ), 27% of HER2-amplified, and 7% of triple-negative cases and is predictive for early relapses and poor outcome (43)(44)(45)(46)(47). Many FGFR1-amplified breast cancer cell lines are addicted to FGFR1 amplification (45,48,49), and FGFR1 amplification also drives resistance to endocrine therapy (48).…”
Section: Dysregulation Of Fgfr Signaling In Human Malignanciesmentioning
confidence: 99%
“…In breast cancer, amplification of FGFR1-and/or 11q12-14 (which contains CCND1, FGF3, FGF4, and FGF19) have been observed in 23% of hormone receptor-positive (HR þ ), 27% of HER2-amplified, and 7% of triple-negative cases and is predictive for early relapses and poor outcome (43)(44)(45)(46)(47). Many FGFR1-amplified breast cancer cell lines are addicted to FGFR1 amplification (45,48,49), and FGFR1 amplification also drives resistance to endocrine therapy (48). FGFR2 amplification (4% of triple-negative breast cancer, 4%-9% of gastric cancers) is associated with the maintenance of tumor-initiating cells (50), poorer prognosis (51,52), and high sensitivity to FGFR inhibitors (49,50,53).…”
Section: Dysregulation Of Fgfr Signaling In Human Malignanciesmentioning
confidence: 99%
“…Always in the context of BC, amplification of FGFR1-and/or 11q12-14, which is a chromosomal region containing CCND1, FGF3, FGF4, and FGF19, have been detected in 23% of hormone receptor-positive (HR+) BC, 27% HER2-positive BC, and 7% TNBC and it has been shown to be a prognostic indicator for early relapses and poor patients' outcome [32][33][34][35][36]. As shown by in vitro studies, the Accordingly to several studies, FGFR2 amplifications -shown to occur in 4% of TNBC-as well as activating mutations of the receptor, have been associated with high sensitivity to FGFR inhibitors [37][38][39] and maintenance of tumour-initiating cells [38].…”
Section: Amplification Of Fgfrsmentioning
confidence: 99%
“…As shown by in vitro studies, the Accordingly to several studies, FGFR2 amplifications -shown to occur in 4% of TNBC-as well as activating mutations of the receptor, have been associated with high sensitivity to FGFR inhibitors [37][38][39] and maintenance of tumour-initiating cells [38]. [24, [32][33][34][35][36][37], which has shown transforming potential in several in vivo models, conferring also sensitivity to FGFR inhibitors [35] and ability to drive resistance to endocrine therapy [24] as previously described; FGFR2 translocation, which in preclinical models exhibited transforming potential and sensitivity to FGFR inhibitors [40]; FGFR2 amplifications (4%, [38]), which in preclinical models conferred resistance to FGFR inhibitors [37][38][39]. In different solid tumors, including breast cancer, various studies in literature have described FGFRs activating mutations: FGFR1: two point mutations (K656E and N546) have observed in vitro affecting the intracellular domain of the receptor and therefore acting as activating mutations [41,42].…”
Section: Amplification Of Fgfrsmentioning
confidence: 99%
“…Это происходит за счет активации матриксной металлопротеина-зы-3 и деградации Е-кадхерина [36]. Последнее является характерной особенностью дольково-го рака молочной железы, а FGFR1 при данном подтипе рака рассматривается как терапев-тическая мишень [37]. Также интересно, что амплификация FGFR1 характерна в большей степени для инвазивного рака, в отличие от карциномы in situ.…”
Section: рак молочной железыunclassified